The antecedents of digital marketing application by Malaysian micro, small and medium enterprises (MSMEs) - Aliman, Nor Khasimah; Zainal Ariffin, Zailin; Hassan, Paiz; Anas, Norazmi (UiTM Cawangan Johor, 2021)
The rapid growth of higher education institutions in Malaysia is parallel with the growing demand of its population pursuing tertiary education. For such reason, universities and other tertiary education providers are constantly challenged in providing sufficient in-campus accommodation to help students living comfortably. Regardless of their continuous effort in improving their facilities, the issue of shortage of students' accommodation persists; thus, boosting the demand for rental properties surrounding campus location. This opens the opportunity for homeowners who own rental units within proximity to a campus location to target students as their potential tenants. Therefore, it is worth the effort for homeowners to understand students‘ preferences when searching/or a rental unit. In line with the stipulated issue, this study aims to investigate university students' perceived perception office relevant criteria 111hen searching for a rental house. This study employed a quantitative research design with a total of 150 respondents were successfully gathered via an online questionnaire. These respondents are off campus students studying at Universiti Teknologi MARA (UiTM) Melaka campus. The result of the descriptive analysis revealed that many of the respondents students as their potential tenants. Therefore, it is worth the effort for homeowners to understand students ‘preferences when searching/or a rental unit. In line with the stipulated issue, this study aims to investigate university students' perceived perception of five relevant criteria 111hen searching for a rental house. This study employed a quantitative research design with a total of 150 respondents were successfully gathered via an online questionnaire. These respondents are off campus students studying at Universiti Teknologi MARA (UiTM) Melaka campus. The result of the descriptive analysis revealed that many of the respondents